Peroxisome proliferator activated receptor‐gamma stimulation for prevention of 5‐fluorouracil‐induced oral mucositis in mice. Issue 3 (20th November 2017) - Sottili, Mariangela; Mangoni, Monica; Gerini, Chiara; Salvatore, Giulia; Castiglione, Francesca; Desideri, Isacco; Bonomo, Pierluigi; Meattini, Icro; Greto, Daniela; Loi, Mauro; Francolini, Giulio; Perna, Marco; et al.
Abstract: Background: Oral mucositis is a side effect of treatment regimens containing 5‐fluorouracil (5‐FU). The purpose of this study was to present our evaluation to see if rosiglitazone (RGZ) protected normal tissues from chemotherapy‐induced oral mucositis. Methods: C57BL/6J mice were treated with 5‐FU for 5 days, with or without RGZ. Mice were euthanized after 5, 8, 11, or 15 days, and mucosal segments were collected. Results: The RGZ did not affect the 5‐FU‐induced decrease in mouse body weight. The 5‐FU caused loss of epithelial architecture, collagen fiber impairment, and inflammatory infiltration. The RGZ reduced leukocyte infiltration, preserved tissue structure, and dampened the 5‐FU‐induced expression of p53 and matrix metalloproteinase ( Mmp ) ‐2 after 5 days, and of Mmp‐2 and interleukin ( Il‐1β after 15 days. The RGZ inhibited the 5‐FU‐induced increase of transforming growth factor‐beta (TGF‐β) and nuclear factor‐kappa B (NF‐κB) proteins and restored collagen protein levels. Conclusion: The RGZ had a protective effect on oral mucosa damaged by chemotherapy. These data encourage the further study of RGZ for the prevention of 5‐FU‐induced mucositis in patients with cancer.